EFFECTIVE TECHNIQUES FOR BUILDING VOCABULARY AMONG INTERMEDIATE LEVEL LANGUAGE LEARNERS TROUGH MOBILE APPLICATIONS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In an increasingly globalized world, linguistic proficiency is rapidly becoming a critical skill for future generations. This article addresses the challenges inherent in vocabulary acquisition, offering a curated selection of online resources designed to streamline and simplify the process of lexical expansion for learners struggling to build their vocabulary.